Choosing Organic Food: Planned Behavior Factors, Health Consciousness, eWOM, and Selective Gender Moderation - Elsa Shafira; Erna Sofriana Imaningsih (ARE Publisher, 2026)
Organic food purchase intention is shaped by attitude, subjective norm, perceived behavioral control, health consciousness, and electronic word of mouth, making it important to test these key determinants together and assess whether the relationships vary by gender. Objectives: This study examines the effects of planned behavior factors (attitude, subjective norm, perceived behavioral control), health consciousness, and electronic word of mouth on organic food purchase intention and tests gender as a moderating variable. Methodology: A quantitative survey was conducted using non-probability purposive sampling, involving 243 respondents. The data were analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM) and gender differences were examined using Multi Group Analysis (MGA). Finding: The results show that attitude, subjective norm, perceived behavioral control, health consciousness, and eWOM positively and significantly influenced purchase intention. Multi Group Analysis confirmed selective gender moderation on the effects of perceived behavioral control and health consciousness, while gender differences were not significant for attitude, subjective norm, and eWOM. Conclusion: Organic food purchase intention is driven by behavioral, health, and online information factors, with gender differences appearing only in perceived behavioral control and health consciousness pathways. Keywords: purchase intention on organic food; theory of planned behavior; health consciousness; electronic word of mouth; gender as moderation